2022
DOI: 10.1155/2022/5817684
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Stem Cell-Derived Small Extracellular Vesicles Promote M2 Macrophage Polarization and Suppress CD4+ T-Cell Activity by Transferring UCA1 and Targeting LAMC2

Abstract: Cancer-derived small extracellular vesicles (sEVs) are emerging as crucial mediators of intercellular communication between cancer cells and M2-tumor-associated macrophages (M2-TAMs) via transferring lncRNAs. We previously reported that miR-134 blocks the expression of its targeting protein LAMC2 via the PI3K/AKT pathway and inhibits cancer stem cell (CSC) migration and invasion in oral squamous cell carcinoma (OSCC). This study hypothesize that OSCC-CSC-derived small extracellular vesicles (OSCC-CSC-sEVs) tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Previous studies indicated that the OSCC/CAFs derived exosomes can be internalized by OSCC cells, and then promote the growth, migration, and invasion of tumor cells by activating PI3K/AKT 16 and MAPK/ERK 17 pathways (Figure 2B). For instance, the highly expressed miRNA-382-5p in CAFs can be transported to OSCC cells via exosomes, thus promoting the invasion of OSCC.…”
Section: Exosomes Mediated the Cell Proliferation Migration And Invas...mentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies indicated that the OSCC/CAFs derived exosomes can be internalized by OSCC cells, and then promote the growth, migration, and invasion of tumor cells by activating PI3K/AKT 16 and MAPK/ERK 17 pathways (Figure 2B). For instance, the highly expressed miRNA-382-5p in CAFs can be transported to OSCC cells via exosomes, thus promoting the invasion of OSCC.…”
Section: Exosomes Mediated the Cell Proliferation Migration And Invas...mentioning
confidence: 91%
“…22 However, relevant studies have also shown that exosomes were involved in immunosuppression. 23 Exosomes extracted from plasma of patients with head and neck cancer could effectively inhibit proliferation of CD4 + T cells, induce apoptosis of CD8 + T cells, accelerate the immunosuppressive ability of regulatory T cells (Treg cells), and weaken the cytotoxicity of natural killer (NK) cells 16 (Figure 2C).…”
Section: Exosomes Mediated Immune Effects On Osccmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs could envelop and transport lncRNA from tumor cells to target cells, consequently influencing the expression of miRNA and changing the tumor microenvironment (TME) [ 142 ]. One of the most representative lncRNAs was HOTTIP, and it caused various changes according to its origin: the M1 macrophage-derived exosomal lncRNA HOTTIP proved to strongly suppressed tumor progression via the upregulation of the TLR5/NF-κB pathway [ 143 ]; however, when it was secreted by cancer stem cells in OSCC, it then promoted M2 macrophage polarization, inhibited CD4+ T-cell proliferation and IFN-γ production, and facilitated tumor progression and immunosuppression via the LAMC2-mediated PI3K/AKT pathway [ 144 ].…”
Section: Ev Cargoes and Their Instructive Effects In Hnsccmentioning
confidence: 99%
“…Other ncRNAs secreted by CSCs could also be potent regulators involved in TME; glioma CSCs release exosomes carrying lncRNA MALAT1, which induces secretion of IL-6 and TNF-α from LPS-stimulated microglia cells. Oral squamous cell carcinoma (OSCC)-CSC-derived EVs transferred miR-134 and consequently promoted M2 macrophage polarization by targeting LAMC2 via the PI3K/AKT pathway in vitro and in vivo [ 112 ]. M2 macrophage-derived exosomal miR-31-5p can inhibit the tumor suppressor LATS2 gene and facilitate the progression of OSCC via inhibiting the Hippo signaling pathway [ 113 ].…”
Section: Introductionmentioning
confidence: 99%